Comparative toxicology in vitreous humor and blood - Sturner, William Q.; Garriott, James C. (Forensic science (Lausanne), 1975)
Drug and toxic substances were detected in blood and vitreous humor in fifty-six cases, in which causes of death were both from an overdose of the particular substances and from other unrelated causes. Five instances are reported in which two drug substances were detected in blood and vitreous humor from the same subject. Patients having long survival times, as well as those dying from unrelated causes, reveal drug values to approach unity, when the blood and vitreous concentrations are compared. The ratios reached at equilibrium probably depend on solubility of the drug in vitreous humor, lipid solubility and the percentage protein-bound in the blood. The vitreous humor provides another parameter of testing and may be useful in studies of survival time.